2013
DOI: 10.1159/000345026
|View full text |Cite
|
Sign up to set email alerts
|

A Weight Loss Diet Intervention Has a Similar Beneficial Effect on Both Metabolically Abnormal Obese and Metabolically Healthy but Obese Premenopausal Women

Abstract: Background/Aims: We studied the effect of a 12-week energy-restricted diet intervention on cardiometabolic risk in two groups of nonmorbid obese premenopausal Caucasian women, i.e. a metabolically abnormal obese (MAO) and a metabolically healthy but obese (MHO) group. Methods: The participants were 53 MAO and 25 MHO women (age range 19-49 years; body mass index inclusion criterion: 30-39.9). We assessed changes in body weight and composition, blood lipids, insulin resistance, hepatic enzymes, inflammatory mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 76 publications
(58 reference statements)
7
27
0
Order By: Relevance
“…Some authors have found higher adiponectin concentrations in MHO as compared with MAO, which has been related to reduced inflammation and improved metabolic function (25,26). The similarly reduced levels observed in the current study have been reported previously (7,27,28) and together with the comparable concentrations of leptin and resistin suggest that MHO and MAO show a very similarly altered adipokine profile. To our knowledge, this is the only study analyzing the circulating concentrations of SAA, VEGF, and MMP9 in MHO subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors have found higher adiponectin concentrations in MHO as compared with MAO, which has been related to reduced inflammation and improved metabolic function (25,26). The similarly reduced levels observed in the current study have been reported previously (7,27,28) and together with the comparable concentrations of leptin and resistin suggest that MHO and MAO show a very similarly altered adipokine profile. To our knowledge, this is the only study analyzing the circulating concentrations of SAA, VEGF, and MMP9 in MHO subjects.…”
Section: Discussionsupporting
confidence: 91%
“…After initial exclusion criteria, 135 papers were assigned for full-text review with 12 articles included for data extraction and analysis [17,18,19,20,21,22,23,24,25,26,27,28] (Figure 2). …”
Section: Resultsmentioning
confidence: 99%
“…The population consists of 1827 subjects and was characterized by a baseline BMI > 30 kg/m 2 , a mean age from 34.4 [18] to 61.1 [20], and representing Caucasian and Asian ethnicities. Time of interventions ranged from 12 to 104 weeks and were based on diet only [18,21,22,23,24,25,26,27] or diet with combination of light to moderate physical activity (PA) [19,20,28] that supported the daily energy deficit. …”
Section: Resultsmentioning
confidence: 99%
“…In 2014, Blüher and Schwarz 100 reviewed and updated the characterization of the MHO individuals and concluded . Based on this definition and using term/abbreviations already used in the literature, this group could be named as MAO 65,66,104,105,[153][154][155] or MUHO. 75,94,101,111,117,156 This definition would be problematic from both a clinical and analytic point of view, how would be considered/ treated those individuals who meet only 1 criteria and are therefore left out from the MHO group and also from the MAO/MUHO group?…”
Section: Characteristics Of Mho Individualsmentioning
confidence: 99%